(untitled) (Communications in Mathematical Research, 2019)
Let F be a family of holomorphic curves of a domain D in C into a closed subset X in P^N(C). Let Q_1(z), …, Q_2t+1(z) be moving hypersurfaces in P^N(C) located in pointwise t-subgeneral position with respect to X. If each pair of curves f and g in F share the set {Q_1(z), …, Q_2t+1(z)}, then F is normal on D. This result greatly extend some earlier theorems related to Montel's criterion.